A fast, accurate method for value-at-risk and expected shortfall - Jochen Krause; Marc S. Paolella (Econometrics, 2014)
A fast method is developed for value-at-risk and expected shortfall prediction for univariate asset return time series exhibiting leptokurtosis, asymmetry and conditional heteroskedasticity. It is based on a GARCH-type process driven by noncentral t innovations. While the method involves the use of several shortcuts for speed, it performs admirably in terms of accuracy and actually outperforms highly competitive models. Most remarkably, this is the case also for sample sizes as small as 250.
Keywords: C51; C53; G11; G17; 330; GARCH; mixture-normal-GARCH; noncentral t; lookup table